2016
DOI: 10.1007/s10899-016-9627-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Adolescent Problem Gambling: A Systematic Review of Recent Research

Abstract: Previous research has shown that gambling is a popular activity among adolescents. Following a rapid expansion of legalized gambling opportunities and the emergence of new forms of gambling, many researchers have carried out studies on adolescent gambling and problem gambling. The present paper reviews studies that have been conducted worldwide since 2000, and then presents a more detailed picture of adolescent gambling research in Europe, by providing a country-by country analysis. After an extensive search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
267
5
22

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 395 publications
(312 citation statements)
references
References 46 publications
18
267
5
22
Order By: Relevance
“…Only one CHO and one Drug Task Force offered services to patients under the age of 18 years. It is known from previous studies that rate of at-risk and gambling disorder to be 4% and 1.2% respectively in the adolescent (aged 14-18 years) population (Gonzalez-Roz et al 2017), although a recent systematic review found a very wide range of problem gambling in adolescence ranging from 0.2% in Norway and Australia to 13% in Croatia (Calado et al 2017). There is also evidence from population surveys in the UK that 12% of adolescents (aged 11-16 years) had gambled in the week prior to taking part in a national survey (Gambling Commission 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Only one CHO and one Drug Task Force offered services to patients under the age of 18 years. It is known from previous studies that rate of at-risk and gambling disorder to be 4% and 1.2% respectively in the adolescent (aged 14-18 years) population (Gonzalez-Roz et al 2017), although a recent systematic review found a very wide range of problem gambling in adolescence ranging from 0.2% in Norway and Australia to 13% in Croatia (Calado et al 2017). There is also evidence from population surveys in the UK that 12% of adolescents (aged 11-16 years) had gambled in the week prior to taking part in a national survey (Gambling Commission 2017).…”
Section: Discussionmentioning
confidence: 99%
“…En España encontramos estudios de carácter regional que apuntan a una prevalencia adolescente al juego del 5,6%, erigiéndose como la más alta de Europa (Calado et al 2017) o de al menos de más del 2% en este grupo especialmente vulnerable (Verdura, 2014, p.10).…”
Section: Digitalmente Vulnerablesunclassified
“…Recent data suggests that adolescents are gambling to an increasing extent [1,2], where 36-79% of adolescents report having gambled over the past year [3][4][5]. Although adults tend to gamble more frequently than adolescents, the prevalence of problem gambling (PG) has been estimated to be two to four times higher in youth aged 12 to 17, with rates of Problem Gambling (PG) ranging from 3% to 8% [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%